2008
DOI: 10.1017/s0022149x08873579
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shell size ofLymnaea columellaon infectivity and development ofFasciola hepatica

Abstract: Experimental infections of Lymnaea columella with Fasciola hepatica were carried out to determine the influence of shell size on the infection rate and on the outcome of rediae and cercariae. Snails were divided into seven groups according to shell size: 2-4 mm, 5-6 mm, 7-8 mm, 9-10 mm, 11-12 mm, 13-14 mm and 15 mm or more. One hundred snails in each group were infected by using four miracidia for each snail. Snails with larger shell size showed a lower infection rate, the groups presenting the highest (79%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These differences might be due to the snail size at the time of exposure. According to Coelho et al (2008), prevalence of F. hepatica infection in snails measuring 15 mm at the time of exposure was lower, at 2%, compared with 79% in snails measuring 5–6 mm. In contrast, Vázquez et al (2013) explained these differences by variability in miracidial infectivity.…”
Section: Discussionmentioning
confidence: 96%
“…These differences might be due to the snail size at the time of exposure. According to Coelho et al (2008), prevalence of F. hepatica infection in snails measuring 15 mm at the time of exposure was lower, at 2%, compared with 79% in snails measuring 5–6 mm. In contrast, Vázquez et al (2013) explained these differences by variability in miracidial infectivity.…”
Section: Discussionmentioning
confidence: 96%
“…Literature has shown that geographical variations in Lymnaea species influence their susceptibility to infections by F. hepatica (Gasnier et al, 2000;Coelho et al, 2008). This has been observed by Gutiérrez et al (2011) and Alba et al (2018), who reported on variations within P. columella species that influenced their susceptibility to F. hepatica infections.…”
Section: Discussionmentioning
confidence: 67%
“…The latter difference might be because O. viverrini s.l. cercariae are an immature stage [14]. The former variations possibly reflect parasite adaptations in different habitat types and relationships to genetic variation [4,46].…”
Section: Discussionmentioning
confidence: 99%